INISIASI MENYUSU DINI (IMD) MEMPERCEPAT PENGELUARAN ASI - Mariati, Mariati (Politeknik Kesehatan Kemenkes Bengkulu, 2012)
Early initiation of breastfeeding is a process of letting the baby breastfeed their own immediately after birth so that it benefits both mother and baby, physically and psychologically. It can safe 22% of neonatal deaths, prevent hipotermi and enhance ties of affection. In the city of Bengkulu implementation of the early initiation of breastfeeding not yet have an impact on exclusive breastfeeding in 2009 (59.1%). The purpose of this study to know the implementation of early initiation of breastfeeding in private practice midwives in the city of Bengkulu.This study design with qualitative methods through an explorative approach to dig more deeply about the situation of implementation of the early initiation of breastfeeding on the midwives who in private practice in the city of Bengkulu. Informants of this study amounted to 12 persons elected by purpose sampling. Data were collected through in-depth interviews and direct observation analyzed by phase: transcripts, coding, and conclusions based on pre-determined category.The results showed all the informants were well versed in the early initiation of breastfeeding, but its implementation has not been done in the most especially when the patients feel tired or lack motivation and family do not support this implementation so that postponed and not taken immediately. Furthermore, this implementation did not result in exclusive breastfeeding because the patient feels there is no milk coming out so it is not important for mothers to keep breastfeeding. The attitude of midwives in the implementation of the early initiation of breastfeeding is quite good and supports the implementation of the early initiation of breastfeeding, especially with seeing the benefits. To improve the implementation of the early initiation of breastfeeding needs to be done counseling since pregnant women and prepare it so that mothers will understand its benefits and to continually feeding that can accelerate spending and prevent breast milk feeding other than breast milk during the month / exclusive